Evaluating the potential of wild cocoyam (Caladium bicolor) for citric acid production in a submerged culture of Aspergillus niger - Ezeaa, Ifeanyi Boniface (2023)
Wild cocoyam (Caladium bicolar) is non-edible starchy material which is commonly known as ‘Ede umuagbara’ in the south-east region of Nigeria. Evaluating the potential of wild cocoyam for citric acid production was investigated using Aspergillus niger in a submerged culture...